2000
DOI: 10.1001/archneur.57.2.225
|View full text |Cite
|
Sign up to set email alerts
|

Differences Between Pick Disease and Alzheimer Disease in Clinical Appearance and Rate of Cognitive Decline

Abstract: There is a characteristic cognitive profile and course of dementia in PcD. Nonetheless, cognitive test performance does not clearly distinguish PcD from AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
1
6

Year Published

2001
2001
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 46 publications
6
51
1
6
Order By: Relevance
“…Patients with FTD declined an average of 30 points on the MDRS over 1 year, double the average 15-point drop for AD patients. This observed disparity in cognitive decline parallels recent findings using clinically diagnosed (Binetti et al, 2000) and autopsy-confirmed (Rascovsky et al, 2005) patient samples. Indeed, a recent multicenter study of autopsy-confirmed patients (Rascovsky et al, 2005) found faster rates of cognitive decline in FTD than AD when cognition was assessed with the Mini-Mental State Examination (MMSE).…”
Section: Cognitive Dysfunction In Ftd 379supporting
confidence: 86%
See 2 more Smart Citations
“…Patients with FTD declined an average of 30 points on the MDRS over 1 year, double the average 15-point drop for AD patients. This observed disparity in cognitive decline parallels recent findings using clinically diagnosed (Binetti et al, 2000) and autopsy-confirmed (Rascovsky et al, 2005) patient samples. Indeed, a recent multicenter study of autopsy-confirmed patients (Rascovsky et al, 2005) found faster rates of cognitive decline in FTD than AD when cognition was assessed with the Mini-Mental State Examination (MMSE).…”
Section: Cognitive Dysfunction In Ftd 379supporting
confidence: 86%
“…It is estimated that approximately 3-20% of all cases of dementia may be FTD (Barker et al, 2002;Gislason et al, 2003;Knopman et al, 1990;Neary, 1999;Ratnavalli et al, 2002;Rosso et al, 2003), and the disorder is particularly prevalent when the age of onset of dementia is younger than 65 years (Ratnavalli et al, 2002;Rosso et al, 2003). Recent studies suggest that FTD follows a particularly malignant course (Grasbeck et al, 2003;Hodges et al, 2003), but information as to the nature and rate of cognitive decline is still scarce (Binetti et al, 2000;Pasquier et al, 2004;Rascovsky et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common behavioral changes include apathy, disinhibition, and inappropriate social conduct. Some studies have shown that the caretaker report of behavioral change is often the best way to differentiate between FTD and AD (Binetti, Locascio, Corkin, Vonsattel, & Growdon, 2000;Gregory et al, 1997). The hallmarked behavioral and functional changes are identified by the caretakers and quantified through their responses on measures like the NPI, Interpersonal Reactivity Index (IRI), Interpersonal Adjectives Scales, and Clinical Dementia Rating Scale (CDR).…”
Section: Differentiation Of Ftd From Admentioning
confidence: 99%
“…symptoms and early changes in behaviour. Some evidence suggests that the symptoms Some evidence suggests that the symptoms at presentation differentiate FTD from Alzat presentation differentiate FTD from Alzheimer's disease (Binetti heimer's disease (Binetti et al et al, 2000;Lindau , 2000;Lindau et al et al, 2000). Investigations are also helpful , 2000).…”
Section: Clinical Features Of Ftd Clinical Features Of Ftdmentioning
confidence: 99%